2014
DOI: 10.1002/cne.23533
|View full text |Cite
|
Sign up to set email alerts
|

Lateral habenula and the rostromedial tegmental nucleus innervate neurochemically distinct subdivisions of the dorsal raphe nucleus in the rat

Abstract: The lateral habenula (LHb) is an epithalamic structure differentiated in a medial (LHbM) and a lateral division (LHbL). Together with the rostromedial tegmental nucleus (RMTg), the LHb has been implicated in the processing of aversive stimuli and inhibitory control of monoamine nuclei. The inhibitory LHb influence on midbrain dopamine neurons has been shown to be mainly mediated by the RMTg, a mostly GABAergic nucleus that receives a dominant input from the LHbL. Interestingly, the RMTg also projects to the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 185 publications
(376 reference statements)
10
72
0
6
Order By: Relevance
“…They also noted, based on a report by Behzadi et al (1990), that LHb projections to the median raphe that take up radiolabeled D-aspartate arise in their LHbMS, which contains neurons that express Fos after persistent noxious stimulation (Nagao et al, 1993). They further cited work indicating that major DA innervation of the LHb is relatively limited to their LHbMPc (Skagerberg et al, 1984), the small-celled site of striking peptidergic enrichments mentioned above, where also neurons in which Fos-immunoreactivity is elicited by daytime stress are concentrated (Chastrette et al, 1991), and which was early reported to be the LHb origin of projections to the dorsal raphe nucleus (Aghajanian and Wang, 1977; Pasquier et al, 1977; Sego et al, 2014). …”
Section: Cytology and Subnucleimentioning
confidence: 99%
See 2 more Smart Citations
“…They also noted, based on a report by Behzadi et al (1990), that LHb projections to the median raphe that take up radiolabeled D-aspartate arise in their LHbMS, which contains neurons that express Fos after persistent noxious stimulation (Nagao et al, 1993). They further cited work indicating that major DA innervation of the LHb is relatively limited to their LHbMPc (Skagerberg et al, 1984), the small-celled site of striking peptidergic enrichments mentioned above, where also neurons in which Fos-immunoreactivity is elicited by daytime stress are concentrated (Chastrette et al, 1991), and which was early reported to be the LHb origin of projections to the dorsal raphe nucleus (Aghajanian and Wang, 1977; Pasquier et al, 1977; Sego et al, 2014). …”
Section: Cytology and Subnucleimentioning
confidence: 99%
“…In any event, the ‘feigned’ DA (but actually GABAergic and glutamatergic) mesohabenular pathway thus may disproportionately affect LHb outputs to the DR, which mainly arise from LHbMC and LHbMPc (Aghajanian and Wang, 1977; Pasquier et al, 1977; Sego et al, 2014). In line with this connectivity, Luo et al (2015) hypothesized that loss of DA neurons in Parkinson’s disease (PD) may produce a disinhibition of LHb neurons (due to loss of GABA transmission), which itself is dysphoric and may, in turn, act to decrease serotonin levels – another deficit likely to be associated with behavioral depression in PD patients.…”
Section: Afferent Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the Vglut3 + serotonergic neurons, a specific subgroup of non-serotonergic Vglut3 + cells is located in the central dorsal raphe. Furthermore, recent studies demonstrated the importance of glutamatergic neurotransmission from the dorsal raphe to ventral tegmental area (VTA) in the regulation of motivation and reward processing (Hioki et al, 2010;Liu et al, 2014;McDevitt et al, 2014;Qi et al, 2014;Sego et al, 2014). Developmental mechanisms underlying the neuronal heterogeneity in the dorsal raphe are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these GABAergic neurons are referred to as dopaminergic neuron-associated GABAergic (D-GABA) neurons . It has been suggested that the RMTg integrates signals from different parts of the brain, including the lateral habenula (LHb), converting them into inhibitory inputs to both DA and 5-HT networks (Lavezzi and Zahm, 2011;Barrot et al, 2012;Bourdy and Barrot, 2012;Proulx et al, 2014;Sego et al, 2014).…”
Section: Introductionmentioning
confidence: 99%